KUALITAS DAN STATUS MUTU AIR IRIGASI UNTUK PADI SAWAH DI SUBAK YEHEMBANG, KABUPATEN JEMBRANA, BALI - I Ketut Sundra (SIMBIOSIS, 2024)
Research on the quality and status of irrigation water has been carried out for lowland rice in the Subak of Yehembang, Jembrana Regency, Bali. The sampling technique was carried out by Purposive Sampling. The analysis was carried out for physical, chemical and microbiological parameters. The level of feasibility of the results are matched with class 1 Water Quality Standards based on the Bali Governor Regulation No. 16 of 2016, while the status of water quality is determined by the Storet Method based on the Decree of the Minister of Environment No. 115 of 2003. The results showed that in the rainy and dry seasons there were 3 parameters namely DO, BOD5, and Coliform Bacteria pass grade 1 water quality standards. For the quality status of Subak yehembang irrigation water for 4 locations during the rainy and dry seasons all are classified as moderately polluted Keywords: subak, irrigation water, water quality, water quality statu.